MANAGEMENT OF PROSTATE CANCER IN ACCRA, GHANA - Yeboah, ED (J West Afr Coll Surg, 2016)
INTRODUCTION: Africans living with prostate cancer in Africa face problems of early diagnosis and appropriate treatment. AIM: To study the clinical incidence of prostate cancer, risk factors, TNM stage, their management and outcomes. METHODS: A prospective study of Prostate Cancer cases managed at Korle Bu Teaching Hospital and hospitals in Accra, diagnosed by history, abnormal PSA/DRE, physical examination and histologically confirmed by biopsy from 2004 to 2013 was carried out. The cases were TNM staged and managed by approved protocol. RESULTS: There were 669 cases with a mean age 70±0.045SE years, median Gleason Score of 7, organ confined Prostate Cancer(PC) in 415(62%), locally advanced in 167(25%) and metastatic Prostate Cancer in 87(13%) cases. The cases were followed for median of 10 months to ≥ 84 months. Organ confined cases were managed by: Radical Prostatectomy (RP) 92 (13.8%) with a mortality of 0.3%; brachytherapy 70 (10.5%) with a mortality of 0.1% and External Beam Radiotherapy (EBRT) 155 (23%) with a mortality 0.7%. In all, 98 men constituting (14.1%) cases with a mean age of 75+0.25SE years, life expectancy <10 years were treated by hormonal therapy with a mortality of 1.7%. Twenty cases who were for active surveillance (GS6), PSA <10ng/ml, life expectancy <10 years later all opted for EBRT. Locally advanced cases 25% all had neoadjuvant hormonal therapy then Brachytherapy in 3 (0.4%) mortality 0.15% and EBRT in 64 (9.5%), mortality 0.59%. Hormonal therapy was given in 100 (15%) locally advanced cases, mortality 5%. Metastatic prostate cancer cases (13%) were managed by hormonal therapy, mortality 6%. CONCLUSION: Improved facilities and dedicated skilled teams led to a significant rise in proportion of organ confined Prostate Cancer from 15.3% to 62% curable by Radical Prostatectomy, brachytherapy or EBRT with longer disease free survival.